2009
DOI: 10.1029/2008ja013759
|View full text |Cite
|
Sign up to set email alerts
|

Global structure and seasonal and interannual variability of the migrating diurnal tide seen in the SABER/TIMED temperatures between 20 and 120 km

Abstract: [1] The present paper is focused on the global spatial (altitude and latitude) structure and seasonal and interannual variability of the migrating diurnal tide derived from the Sounding of the Atmosphere using Broadband Emission Radiometry/ThermosphereIonosphere-Mesosphere-Energetics and Dynamics (SABER/TIMED) temperature measurements for 6 full years (January 2002 to December 2007. The tidal results are obtained by a new analysis method where the tides (migrating and nonmigrating) and the planetary waves (zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
125
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 59 publications
14
125
1
Order By: Relevance
“…The present paper is going to report the climatological features of the migrating semidiurnal temperature tide produced for latitudes between 50 • N and 50 • S for the period of time between January 2002 and December 2007. Recently a complementary study of the migrating diurnal temperature tide based on the same SABER measurements has been presented by Mukhtarov et al (2009). It is worth mentioning that some main features of the migrating diurnal and semidiurnal temperature tides have been already reported by Zhang et al (2006) and Forbes et al (2008).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The present paper is going to report the climatological features of the migrating semidiurnal temperature tide produced for latitudes between 50 • N and 50 • S for the period of time between January 2002 and December 2007. Recently a complementary study of the migrating diurnal temperature tide based on the same SABER measurements has been presented by Mukhtarov et al (2009). It is worth mentioning that some main features of the migrating diurnal and semidiurnal temperature tides have been already reported by Zhang et al (2006) and Forbes et al (2008).…”
Section: Introductionmentioning
confidence: 82%
“…The tidal results have been obtained by a new analysis method where the tides (migrating and nonmigrating) and the planetary waves (zonally travelling, zonally symmetric and stationary) are simultaneously extracted from the satellite data. The detailed description of this method has been presented in the complimentary study of the migrating diurnal tide reported by Mukhtarov et al (2009) and here it was only briefly summarized. The method for defining the reference noise level for the tidal waves has been briefly mentioned as well.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…See Huang et al (2008aHuang et al ( , 2010aHuang et al ( , b, 2014. Studies by others using SABER temperature (diurnal tides) include Zhang et al (2006) and Mukhtarov et al (2009). Nath and Sridharan (2014) have also derived results of response to solar variability using SABER data at 10-15 • latitude (see Sect.…”
Section: Data Characteristics and Analysismentioning
confidence: 99%
“…So it does not appear that they have considered variations with local time (diurnal variations, tides) in their regression analysis. For both ozone and temperature, diurnal variations are relatively small below ∼ 40 km but can be the dominant form of variations in the mesosphere and lower thermosphere (see Zhang et al (2006), Mukhtarov et al (2009), andHuang et al (2010a) for temperature and Huang et al (2008band Huang et al ( , 2010b for ozone). Even in the stratosphere, variations with local time may not be negligible.…”
Section: Comparison With Previous Saber Analysismentioning
confidence: 99%